On the colours of odours - Jacquot, M; Noel, F; Velasco, C; Spence, C (Springer, 2016)
In the present study, we explore the existence of cross-cultural differences in odour-colour correspondences between two European countries with geographic proximity and shared history: England and France. Moreover, we test whether a single chromatic arrangement can be used to represent an odour in both countries, even if the odour-colour association for this odour differed. The responses of 59 British and 60 French participants to the same set of odorants were compared. Significant colour characterizations were observed for each and every one of the odours tested in both populations. Moreover, both commonalities and differences were reported between the two populations in terms of the odour-colour associations that they exhibited. In the second part of the study, the ability of “chromatic cards” to represent odours was tested. Those “chromatic cards” are objective coloured arrangements generated by a new patented scientific tool developed at Lorraine University (patent FR n°1255688). This tool is based on a neural network algorithm for colour forecasting. It generates a chromatic card that represents any odour from its chemical composition and sensory description. In this study, participants were presented with three cards obtained from an analysis of lavender, cucumber, and peppermint odours. First, the participants had to name the odour evoked by each card. Next, they selected from amongst three different olfactory stimuli the one that best matched each card. The chromatic representations evoked the appropriate odour percept and were significantly associated to their related odours in both of the populations. These findings highlight the existence of common colour representations of odours amongst French and British participants, though some differences were also found. Despite these differences, we were able to validate the relevancy of using single chromatic arrangements in both countries in order to communicate odour information. The latter result may open-up the way for a number of potentially important applications in the design and marketing of both food and non-food products.